C-Phycocyanin protects against mitochondrial dysfunction and oxidative stress in parthenogenetic porcine embryos. Issue 1 (December 2017) - Niu, Ying-Jie; Zhou, Wenjun; Guo, Jing; Nie, Zheng-Wen; Shin, Kyung-Tae; Kim, Nam-Hyung; Lv, Wen-Fa; Cui, Xiang-Shun
Abstract C-Phycocyanin (CP) is a biliprotein enriched in blue-green algae that is known to possess antioxidant, anti-apoptosis, anti-inflammatory, and radical-scavenging properties in somatic cells. However, the protective effect of CP on porcine embryo developmental competencein vitro remains unclear. In the present study, we investigated the effect of CP on the development of early porcine embryos as well as its underlying mechanisms. Different concentrations of CP (2, 5, 8, 10 μg/mL) were added to porcine zygote medium 5 duringin vitro culture. The results showed that 5 μg/mL CP significantly increased blastocyst formation and hatching rate. Blastocyst formation and quality were significantly increased in the 50 μM H2 O2 treatment group following 5 μg/mL CP addition. CP prevented the H2 O2 -induced compromise of mitochondrial membrane potential, release of cytochrome c from the mitochondria, and reactive oxygen species generation. Furthermore, apoptosis, DNA damage level, and autophagy in the blastocysts were attenuated by supplementation of CP in the H2 O2 -induced oxidative injury group compared to in controls. These results suggest that CP has beneficial effects on the development of porcine parthenotes by attenuating mitochondrial dysfunction and oxidative stress.